(untitled) (Bangladesh Journal of Botany, 2021)
Regardless of land use, the results indicated significant differences in all the studied parameters. Total % SOC ranged from 0.52 to 0.72 for conventional farm samples (mean 0.62%) and 0.63 to 1.59 for the organic samples (mean 1.19). Bulk density (g/cc) ranged from 0.43 to 0.81 (mean 0. 62) for conventional and 0.17 to 0.28 (mean 0.20) organic farm soils. Organic manures increased microbial biomass carbon by 117% and dissolved organic carbon (DOC) concentration by 181% over conventional farming. The results suggested that organic matter is better protected in organic soils and are consequently less vulnerable to mineralization.